Montmorillonite, a Promising New Material for Acute Lithium Intoxication in Rats: Montmorillonite in acute lithium intoxication - Moshiri, Mohammad; Imenshahidi, Mohsen; Moallem, Syed Adel; Ghadiri, Ameneh; Nyasmand, Abbas; Mirhoseini Moosavi, Parisa; Gorji Valokola, Mahmoud; Etemad, Leila (Iranian Journal of Pharmaceutical Sciences, 2021)
Lithium (Li) is considered the first-choice treatment for bipolar disorder and has a narrow therapeutic index therefore, a small increase in dose or plasma level can cause toxic effects. Gastrointestinal (GI) decontamination can be regarded as a first-line therapy for acute Li poisoning. Montmorillonite (MMT) is one of the best-known examples of a nanoclay that possesses unique properties for adsorbing substances, especially metals. We investigated the effects of MMT against acute Li intoxication. A single dose of Li (10 mEq/kg) was administered to the rats orally followed by oral gavage of MMT suspensions (0.5 or 1.0 g/kg) or activated charcoal (AC) (1g/kg) 5 min later. The serum Li concentration was measured at different times after treatment. Indeed, the serum level of sodium and potassium, WBC count, activity score, electrocardiogram, brain pathology changes, as well as pharmacokinetic parameters of Li, were evaluated. MMT at higher doses decreased the area under the curve (AUC), the elimination rate constant (Ka), the relative bioavailability (F), and increased the clearance of Li (P<0.05). MMT prevented Li induced leukocytosis, at the first sampling time, (P<0.05). It also exerted significant cardio protection, restored Li-induced ECG changes, heart rate alterations (P<0.001), and prevented Li induced hypoactivity. A similar amount of serum sodium and potassium concentration was observed in the animals. The results indicated that MMT reduced the absorption of Li, and slao possibly increased its clearance. Therefore, MMT may be a good candidate for decontamination, especially substances that are not well adsorbed by AC.